2022
DOI: 10.3389/fimmu.2022.925290
|View full text |Cite
|
Sign up to set email alerts
|

Immunogenic Cell Death and Role of Nanomaterials Serving as Therapeutic Vaccine for Personalized Cancer Immunotherapy

Abstract: Immunogenic cell death (ICD) is a rapidly growing research area representing one of the emerging therapeutic strategies of cancer immunotherapy. ICD is an umbrella term covering several cell death modalities including apoptosis, necroptosis, ferroptosis and pyroptosis, and is the product of a balanced combination of adjuvanticity (damage-associated molecular patterns and chemokines/cytokines) and antigenicity (tumor associated antigens). Only a limited number of anti-cancer therapies are available to induce IC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 161 publications
0
19
0
Order By: Relevance
“…One can see thus that polyelectrolyte multilayer capsules have become an indispensable part of materials research and biosciences; capsules can be used to solve many problems and develop new and emerging applications of nanomaterials. 483 Following the above-outlined possibilities for applying PEM capsules to diverse fields, several challenges still remain. Further research is needed for development of biocompatible and biodegradable polymers, particularly those with a positive charge; controlling monodispersity and sizes of templates; preventing aggregation of templates and capsules particularly in the small size-range; automation of the preparation of PEM capsules; and a more detailed understanding of the LbL assembly at the nanoscale, 484 where essential efforts have been put by the founder of this area Prof. Helmuth Mo ¨hwald.…”
Section: Discussionmentioning
confidence: 99%
“…One can see thus that polyelectrolyte multilayer capsules have become an indispensable part of materials research and biosciences; capsules can be used to solve many problems and develop new and emerging applications of nanomaterials. 483 Following the above-outlined possibilities for applying PEM capsules to diverse fields, several challenges still remain. Further research is needed for development of biocompatible and biodegradable polymers, particularly those with a positive charge; controlling monodispersity and sizes of templates; preventing aggregation of templates and capsules particularly in the small size-range; automation of the preparation of PEM capsules; and a more detailed understanding of the LbL assembly at the nanoscale, 484 where essential efforts have been put by the founder of this area Prof. Helmuth Mo ¨hwald.…”
Section: Discussionmentioning
confidence: 99%
“…As a new method of immunotherapy, immunogenic cell death (ICD) uses inactive cancer cells as cell-based vaccines [ 51 ]. The immunogenicity of ICD is mainly mediated by DAMP and cytokines/chemokines, which are recognized by the corresponding pattern recognition receptors, leading to the activation of the immune systems [ 52 ]. It has been demonstrated that CAR-T cell therapy and immune therapy based on ICD could increase immune infiltration, which has great prospects in the treatment of pancreatic cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Mechanisms Designs PDT Photosensitizers produce ROS under light irradiation Relieve tumor hypoxia [87,88] Increase tumor uptake [79] Combine immunotherapy [89,90] SDT Sonosensitizer produce ROS under ultrasonic irradiation Increase the degree of inertial cavitation [80] Increased targeting [91][92][93][94] Disrupting the redox balance in the cell [95] CDT Fenton reaction produce ROS Metal based nanomaterials [81] CT Anthracyclines induce CRT exposure and ROS production: DOX, Oxp, mitoxantrone, and so on Responsive nanoplatforms as drug carriers [82,84,[96][97][98][99] PTT Photothermal effect Photothermal nanomaterials [83,[100][101][102] Other regulation modes Gas therapy: hydrogen (H 2 ), nitric oxide (NO), carbon monoxide (CO), hydrogen sulfide (H 2 S), sulfur dioxide (SO 2 ), and so on induce ERS Gas nanogenerator [103][104][105][106][107] Calcium ion regulation Calcium ions overload [85] cells including myeloid-derived suppressor cells (MDSCs) and regulatory cells (Tregs), whereas it increased cytotoxic T lymphocytes to enhance ICD.…”
Section: Treatment Modesmentioning
confidence: 99%